CO2,gas-H2Oliquid isotope exchange rates up to 150°C: experimental study and application to hydrothermal CO2 - Kalb, Maximilian; Kluge, Tobias; Eckhardt, Henrik; Weise, Andreas; Prokhorov, Ivan; Kraml, Michael; Eiche, Elisabeth; Neumann, Thomas (Geochimica et cosmochimica acta, 2020)
CO2 isotopologues of hydrothermal origin may yield unique information about the hydrothermal system such as the reservoir temperature or advection velocities. The full understanding of the isotopic signal of CO2 from hydrothermal systems, however, is linked to a good knowledge of the isotopic re-equilibration behaviour. In the last decade multiply-substituted isotopologues of CO2 (i.e. Δ47) emerged as a new tracer that is particularly promising for determining equilibration or source temperatures. Using Δ47 values as proxy for hydrothermal systems relies on the assumption that Δ47 reflects the temperature of the CO2 source at equilibrium conditions. In cases where isotope values change with time, such as during fluid advection across a temperature gradient, the precise knowledge of isotope re-equilibration time scales is a fundamental requirement for the correct evaluation and interpretation of transient signals. Re-equilibration smoothes or even erases the original source signal. We conducted a suite of laboratory experiments on CO2 in contact with liquid water and determined the re-equilibration rate constants between 25°C and 150°C for oxygen (δ18O) and clumped isotopes (Δ47) of CO2. The rate constants k for both isotope tracers are indistinguishable within the studied temperature range and are used as basis for the case study on CO2 of hydrothermal origin. The Δ47 values of the investigated hydrothermal waters generally correspond to the discharge temperature. Δ47 values of CO2 from water at a deep geothermal system were higher than expected for bottom hole temperatures and lower than for the well head discharging water temperature and reflect the continuous re-equilibration during the ascent of the water.